2009
DOI: 10.1016/j.febslet.2009.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Rapid down‐regulation of mitochondrial fat metabolism in human muscle after training cessation is dissociated from changes in insulin sensitivity

Abstract: a b s t r a c tThe association between impairment in mitochondrial muscle fat oxidative capacity (OX FA ) and occurrence of insulin resistance was examined in 14 healthy trained men (age, 24 ± 4 yr) submitted to 4 weeks of training cessation. Training stop induced a significant decrease in mRNA levels of proteins involved in muscle fat metabolism, particularly PPARa (À58%, P < 0.01) and PGC-1a (À30%, P < 0.05), a 21% reduction in OX FA (P < 0.01), and reduced fat oxidation during moderately intense exercise (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Given that insulin is known to decrease FA oxidation (Dyck et al 2001;Kelly et al 2008), the rise in several markers of oxidative capacity observed with low RIP140 might be expected to be associated with lower rates of insulin-mediated FA oxidation. In contrast to those expectations, but in line with data obtained by others, our FA oxidation results indicate that a general improvement in oxidative capacity is not necessarily associated with a larger insulin response (Hancock et al 2008;Rimbert et al 2009;Irving et al 2011).…”
Section: Figure 4 Effects Of Rip140 Downregulation On Mrna Expressionsupporting
confidence: 89%
“…Given that insulin is known to decrease FA oxidation (Dyck et al 2001;Kelly et al 2008), the rise in several markers of oxidative capacity observed with low RIP140 might be expected to be associated with lower rates of insulin-mediated FA oxidation. In contrast to those expectations, but in line with data obtained by others, our FA oxidation results indicate that a general improvement in oxidative capacity is not necessarily associated with a larger insulin response (Hancock et al 2008;Rimbert et al 2009;Irving et al 2011).…”
Section: Figure 4 Effects Of Rip140 Downregulation On Mrna Expressionsupporting
confidence: 89%
“…Similarly, athletes that undergo training cessation often experience perturbations in insulin sensitivity and glucose homeostasis (39 -41). These periods of relative insulin resistance are preceded by a reduction in PGC-1␣, carnitine palmitoyltransferase 1b, and citrate synthase gene expression along with reduced mitochondrial lipid oxidation (42). Reduced muscle lipid oxidation in combination with elevated IMCL, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The overall quality of the reporting of individual study results, including statistical significance, was poor amongst the manuscripts included in this review. Reporting of estimates of the random variability in the data relating to the main outcome only occurred in nine studies (Kiens et al, ; Mensink et al, ; Arkinstall et al, ; Schenk and Horowitz, ; Helge et al, ; Fu et al, ; Rimbert et al, ; Newsom et al, ; Cheng et al, ), and actual P ‐values were only reported in five manuscripts (Tunstall et al, ; Mensink et al, ; de Bock et al, ; Fu et al, ; Newsom et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…EX+DIET using a high‐fat diet increased expression by 215%, significantly greater than a high‐CHO diet (Cameron‐Smith et al, ). Two studies investigating de‐training both reported no significant change (Rimbert et al, ; Bergouignan et al, ).…”
Section: Resultsmentioning
confidence: 99%